La danza folclórica como estrategia en el desarrollo socioemocional de los niños de educación inicial de la Unidad Educativa Ignacio Flores - Albán Constante, Jackeline Estefanía (2022)
There are different activities that can be carried out for the socioemotional development of children in early education, which is why we have taken into account the folkloric dance being this the topic that has caused interest to be investigated, looking for a positive benefit through a part of art focusing on infants who are those who are exposed to various situations within a social group fail to express all their emotions either by shame, fear or other causes, The main objective was to identify the influence that folkloric dance has on the socioemotional development of children in early education at the "Ignacio Flores" Educational Unit. This is a descriptive-exploratory type of research with a non-experimental design and a qualitative-quantitative approach because we worked with numerical data, The analysis of the study sample, which is represented by 28 boys and 16 girls aged 4 to 5 years, was carried out by applying an observation form endorsed by experts, with which we proceeded to demonstrate the social impact generated in the development of the research and in the future, thus being a type of pedagogical strategy that seeks to help children to improve their socioemotional development through the promotion of empathy, For this reason it is worth mentioning that this research has a great social impact and at an educational level this pedagogical strategy has several educational points that could contribute to the growth and socio-emotional development of children.